Avaliação da eficácia da triancinolona intravítrea na preservação de células ganglionares de retina em um modelo de neuropatia óptica Isquêmica anterior em ratos - Pereira, Luciano de Sousa (2017)
Non-arteritic anterior ischemic optic neuropathy (NAION) is the most common acute optic neuropathy in patients over fifty years of age. Management centers around prevention of second eye involvement, without uniformly accepted therapeutic intervention for the involved eye. Several researchers have assessed the benefit of steroids with conflicting results. Animal models based on selective photothrombosis of the microcirculation within the optic nerve head have contributed both to a better understanding of pathophysiological mechanisms associated to NAION; also, it has enabled the testing of potential therapeutic approaches. This study was deisigned to evaluate the efficacy of a single intravitreal triamcinolone acetonide injection (IVTA) in preserving retinal ganglion cells (RGCs) in a rodent model of anterior ischemic optic neuropathy (rNAION). Rodent NAION (rNAION) was induced in female Wistar rats. Animals were randomized into three groups: 1) untreated, 2) treated with 56 μg IVTA, and 3) treated with placebo (intravitreal saline). Procedures were performed in the left eye, with the right eye serving as an internal control. After 30 days, animals were sacrificed and eyes were assessed histologically for RGC number. The average number of RGCs was significantly higher in the control group when compared to rNAION subgroups (p < 0.001). No significant difference was seen between rNAION eyes treated with IVTA, placebo, and untreated eyes (P > 0.05%). In this rodent model for NAION, no therapeutic benefit of intravitreal steroid injection was identified.